An impact of dietary intervention on blood pressures among diabetic and/or hypertensive patients with high cardiovascular disorders risk in northern Thailand by cluster randomized trial. (22nd September 2020) - Yokokawa, Hirohide; Yuasa, Motoyuki; Nedsuwan, Supalert; Moolphate, Saiyud; Fukuda, Hiroshi; Kitajima, Tsutomu; Minematsu, Kazuo; Tanimura, Susumu; Marui, Eiji
Abstract: Background: Global sodium intake remains above the recommended levels to control blood pressure (BP). We aimed to evaluate the efficacy of a dietary intervention on BP through salt reduction among community‐dwelling participants with high risk of cardiovascular disorders (CVD). Methods: This cluster randomized trial (February 2012 to January 2013) included cooking instruction using the pocket salt meter among patients with diabetes and/or hypertension who were treated at health center in Thailand. Based on health centers, 8 clusters of eligible participants were randomly allocated to the 4 intervention and 4 control groups. Dietary intervention was performed at baseline, 1 month, and 3 months in intervention group. In both groups, systolic and diastolic BPs, and estimated 24 hours salt intake based on overnight urine samples were measured at baseline, 6 months, and 12 months. Results: A total of 753 participants were enrolled (374 in the intervention group and 379 in the control group). In the mixed‐effects model, there were significant difference in SBP and estimated salt intake after adjusting covariates at 6 months (adjusted differences between groups [95% CI]; −7.55 [−5.61 to −9.49] mm Hg P  < .01; −0.66 [−0.40 to −0.92] g/day P  = .03). However, these differences were not observed at 12 months (adjusted differences between groups [95% CI]; −1.83 [0.34 to −4.00] mm Hg P  = .48; −0.42 [−0.17 to −0.67] g/day P  = .16). There were no differences in DBP in both follow‐ups. Conclusions: These results may suggest the effectiveness of a visually based dietary intervention targeting salt intake reduction in short term, but the effectiveness discontinued in long term. Clinical trial number: The International Standard Randomized Controlled Trial Number Register (ISRCTN39416277) on January 3, 2012. Abstract : Our cluster randomized trial data revealed the effectiveness of a dietary intervention combining cooking instruction with visualization of estimated salt intake in reducing salt intake. This type of dietary intervention targeting salt intake reduction may contribute to BP management.